ANALISIS MAQASID SYARIAH JASSER AUDA TERHADAP DISKRIMINASI GENDER PADA REVISI UNDANG-UNDANG TENTARA NASIONAL INDONESIA - Safitri, Kanza Indah; Santoso, Amin Nugrah; Zaelani, Abdul Qadir; Djausar, Jayusman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines forms of gender discrimination in the Revision of the Indonesian National Armed Forces Law through the lens of Jasser Auda’s Maqasid al-Shariah and the concept of mubadalah (reciprocity). The revision of the Indonesian National Armed Forces Law has sparked debate concerning gender discrimination that hinders justice and equality between men and women, with implications for social structures and the values of justice in family law. The revised law reflects gender bias through the restriction of strategic positions for women, the construction of domestic roles as female identifiers, and regulations concerning marital status and marriage permits for members of the Indonesian National Armed Forces.This study aims to analyze the forms of gender discrimination in the revised law through the perspective of Maqasid al-Shariah as articulated by Jasser Auda, and its relevance to the principle of justice in Islamic family law. The research employs a normative-comparative approach, examining the academic manuscript of the law revision, classical and contemporary fiqh literature, and Jasser Auda’s maqasid framework, which is holistic, systemic, and oriented toward public welfare (maslahah). The findings indicate that the provisions within the revised law remain grounded in a patriarchal paradigm consistent with traditional social structures in family law, where women are often positioned as secondary actors in both public and private spheres. From Jasser Auda’s perspective, the principles of maqasid must be directed toward achieving al-‘adl (justice), al-karamah al-insaniyyah (human dignity), and taṭawwur (social transformation) as expressions of hifẓ al-nafs (protection of life), hifẓ al-‘aql (protection of intellect), and hifẓ al-nasl (protection of lineage). Therefore, gender discrimination in the Revised TNI Law contradicts the modern maqasid paradigm, which emphasizes the integration of law and social reality. Reformulating military legal policy must integrate the values of gender justice as emphasized in Jasser Auda’s maqasid framework so that national positive law and Islamic family law can harmoniously work together in realizing maslahah (public welfare) and substantive equality.